2023
DOI: 10.21203/rs.3.rs-3482311/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with bacterial sexually transmitted infection screening uptake and diagnosis among men who have sex with men in France

Cheick Haïballa KOUNTA,
Emilie CHAZELLE,
Youssoufa M. OUSSEINE
et al.

Abstract: Background The prevalence of syphilis, Chlamydia trachomatis (CT), and Neisseria gonorrhoeae (NG) in men who have sex with men (MSM) is very high. As these bacterial sexually transmitted infections (bSTIs) are frequently asymptomatic, they are often undiagnosed and therefore untreated. We aimed to characterize the profile of MSM who reported bSTI screening and diagnosis in the previous 12 months, and to identify the factors associated with a diagnosis of a bSTI among MSM in France. Methods We used data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the present study, participants were younger in 2021 than in 2020 and 2022. As French public health data showed that between 2019 and 2021, the screening rate for C. trachomatis infection was higher among men younger than 26 years than among older men [21], we hypothesise that young people may have been more inclined to postpone visiting any medical centre and delayed seeking healthcare during the Covid-19 pandemic, which would allow untreated infections to spread. In 2021, these individuals may have returned to the STI screening centres.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, participants were younger in 2021 than in 2020 and 2022. As French public health data showed that between 2019 and 2021, the screening rate for C. trachomatis infection was higher among men younger than 26 years than among older men [21], we hypothesise that young people may have been more inclined to postpone visiting any medical centre and delayed seeking healthcare during the Covid-19 pandemic, which would allow untreated infections to spread. In 2021, these individuals may have returned to the STI screening centres.…”
Section: Discussionmentioning
confidence: 97%